Saturn's Open‐Closed Field Line Boundary: A Cassini Electron Survey at Saturn's Magnetosphere. Issue 12 (7th December 2019) - Jasinski, Jamie M.; Arridge, Christopher S.; Bader, Alexander; Smith, Andrew W.; Felici, Marianna; Kinrade, Joe; Coates, Andrew J.; Jones, Geraint H.; Nordheim, Tom A.; Gilbert, Lin; Azari, Abigail R.; Badman, Sarah V.; et al.
Abstract: We investigate the average configuration and structure of Saturn' s magnetosphere in the nightside equatorial and high‐latitude regions. Electron data from the Cassini Plasma Spectrometer' s Electron Spectrometer (CAPS‐ELS) is processed to produce a signal‐to‐noise ratio for the entire CAPS‐ELS time of operation at Saturn' s magnetosphere. We investigate where the signal‐to‐noise ratio falls below 1 to identify regions in the magnetosphere where there is a significant depletion in the electron content. In the nightside equatorial region, we use this to find that the most planetward reconnection x‐line location is at 20–25 RS downtail from the planet in the midnight to dawn sector. We also find an equatorial dawn‐dusk asymmetry at a radial distance of >20 RS, which may indicate the presence of plasma‐ depleted flux tubes returning to the dayside after reconnection in the tail. Furthermore, we find that the high‐latitude magnetosphere is predominantly in a state of constant plasma depletion and located on open field lines. We map the region of high‐latitude magnetosphere that is depleted of electrons to the polar cap to estimate the size and open flux content within the polar caps. The mean open flux content for the northern and southern polar caps are found to be 25 ± 5 and 32 ± 5 GWb, respectively. The average location of the open‐closed field boundary is found at invariant colatitudes of 12.7 ± 0.6° and 14.5 ± 0.6°. The northern boundary is modulated by planetary period oscillations more than the southern boundary. Key Points: The high‐latitude magnetosphere is predominantly in a state of constant plasma depletion and located on open field lines The reconnection x‐line is located at 20–25 RS downtail from the planet on the midnight to dawn side of the equatorial magnetosphere The open‐closed field boundary is located at colatitudes of 12.7 ± 0.6° and 14.5 ± 0.6° (north and south) with weak planetary period oscillation modulation in the north